PENERAPAN METODE BERCERITA BAGI KEMAMPUAN NUMERASI SISWA USIA DINI DALAM PEMBELAJARAN TEMATIK [APPLICATION OF THE STORY METHOD FOR EARLY STUDENT NUMERATION ABILITY IN THEMATIC LEARNING] - Sarwuna, Yostinawely; Ani, Yubali; Soesanto, Robert Harry (Universitas Pelita Harapan, 2023)
Based on the results of observations made at a Christian Kindergarten in Tangerang, it was found that there was an unevenness in the numeracy abilities of early-age students. Some students already have the ability to count numbers 1 and 3, but some others do not. Therefore, it is necessary to introduce numeracy skills by the teacher so that students have an even numeracy ability. The purpose of writing this scientific work is to describe the application of the storytelling method to the numeracy skills of early-age students in thematic learning. The research method used is descriptive qualitative research method. Based on the results of the discussion, it was found that the application of the storytelling method was carried out in six stage’s that were closely related to the introduction of numeracy skills, namely making preparations before learning, checking readiness and providing motivation to students, actively involving students, telling stories with attention to language, developing, and checking student understanding. Through the application of the six stages of the storytelling method in thematic learning it can help teachers to assess and confirm the level of numeracy abilities of early age students. The next suggestion is to pay attention to various indicators of numeracy skills that have not been studied and to pay attention to the time allocation in teaching so that the effectiveness of the six stages of the storytelling method can be assessed.BAHASA INDONESIA ABSTRACT: Berdasarkan hasil observasi yang dilakukan pada salah satu Taman Kanak-kanak Kristen di Tangerang ditemukan ketidakrataan kemampuan numerasi siswa usia dini. Beberapa siswa telah memiliki kemampuan membilang bilangan 1 dan 3 namun beberapa lainnya belum. Oleh sebab itu, diperlukan pengenalan kemampuan numerasi oleh guru agar siswa memiliki kemampuan numerasi yang merata. Tujuan penulisan karya ilmiah ini adalah memaparkan penerapan metode bercerita bagi kemampuan numerasi siswa usia dini dalam pembelajaran tematik. Metode penelitian yang digunakan adalah metode penelitian deskriptif kualitatif. Berdasarkan pemaparan hasil pembahasan ditemukan penerapan metode bercerita dilakukan dalam enam tahapan yang berkaitan erat dengan pengenalan kemampuan numerasi yaitu melakukan persiapan sebelum pembelajaran, mengecek kesiapan dan memberikan motivasi kepada siswa, melibatkan siswa secara aktif, bercerita dengan memperhatikan bahasa, melakukan pengembangan, dan mengecek pemahaman siswa. Melalui penerapan keenam tahapan metode bercerita dalam pembelajaran tematik dapat membantu guru untuk menilai serta mengkonfirmasi tingkatan kemampuan numerasi siswa usia dini. Adapun saran selanjutnya adalah memperhatikan berbagai indikator kemampuan numerasi yang belum dikaji serta memerhatikan alokasi waktu dalam melakukan pengajaran sehingga keenam tahapan metode bercerita dapat dinilai keefektifannya.